Penilaian Kinerja Kepala Sekolah dalam Mewujudkan Akuntabilitas di SMPN 34 Surabaya - Savitri, Salma; Pratama, Selviana Alifvia Wahyu; Putra, Sandi Mirza; Trihantoyo, Syunu; Nuphanudin, Nuphanudin (Lembaga Yasin AlSys, 2024)
Assessing the performance of school principals as learning leaders is a necessity that can provide positive, constructive and productive value for school principals and schools in improving school accountability and quality. The performance assessment of school principals is carried out to provide input, guidance and professional development for school principals. The performance assessment of school principals provides information on a map of the strengths and weaknesses of each principal, as a basis for coaching, transfers, promotions and demotions. This research aims to examine how principal performance assessments are carried out in schools that implement an independent curriculum. The research method used is a case study with a qualitative approach. Data was collected through interviews, observation and documentation from SMPN 34 SURABAYA. Observations were carried out to see directly the learning process, interactions and school environment based on the independent curriculum. Documentation is carried out to collect data related to the principal's performance assessment, such as instruments, procedures, results and follow-up. The assessment of the principal's performance also involves various parties, such as teachers, students, parents, school committees and the community. The conclusion of this research is that assessing the performance of school principals as learning leaders can encourage school accountability and quality in implementing the independent curriculum.